2023
DOI: 10.3390/applmicrobiol3020038
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic-Based Sanitation in the Built Environment—An Alternative to Chemical Disinfectants

Abstract: The use of conventional chemical disinfectants is a common practice in built environments and has drastically increased in response to the COVID-19 pandemic. While effective for instantaneous disinfection, the application of chemical disinfectants to indoor surfaces is associated with recontamination and is prone to select for antimicrobial-resistant pathogens. In contrast, probiotic-based sanitation (PBS) relies on the premise that probiotic bacteria, namely apathogenic Bacillus spp., when combined with eco-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…The 32 publications noted in Table 1 ( Falagas and Makris, 2009 ; Manning et al, 2009 ; Kohli, 2013 ; Vandini et al, 2014a , b ; Arvanitakis, 2015 ; La Fauci et al, 2015 ; Caselli et al, 2016 ; Afinogenova et al, 2018 ; Al-Marzooq et al, 2018 , 2019 ; Caselli et al, 2018 ; D'Accolti et al, 2018 , 2019 , 2021 , 2022 , 2023 ; Rodolfi and Caselli, 2018 ; Caselli et al, 2019 ; Dural-Erem et al, 2019 ; Kleintjes et al, 2019 ; Rognoni et al, 2019 ; Caselli and Purificato, 2020 ; Kleintjes et al, 2020 ; Razenberg et al, 2020 ; Stone et al, 2020 ; Tarricone et al, 2020 ; Klassert et al, 2022 ; Soffritti et al, 2022 ; Caselli, 2023 ; Leistner et al, 2023 ; Ramos and Frantz, 2023 ) include an opinion ( Falagas and Makris, 2009 ), two patents ( Manning et al, 2009 ; Rodolfi and Caselli, 2018 ), a commentary ( Caselli and Purificato, 2020 ), a report ( Razenberg et al, 2020 ), two reviews ( D’Accolti et al, 2022 ; Ramos and Frantz, 2023 ), two book chapters ( Kohli, 2013 ; Arvanitakis, 2015 ), three conference abstracts of previously published results ( Al Marzooq et al, 2019 ; Rognoni et al, 2019 ; Caselli, 2023 ), and in vitro assays and hospital-based studies. A total of five publications assessed the efficiency of microbial-based sanitization products using in vitro assays with common healthcare-associated pathogens ( La Fauci et al, 2015 ; D'Accolti et al, 2018 , 2021 ; Dural-Erem et al, 2019 ; Stone et al, 2020 ).…”
Section: Search Strategy and Results Of Literature Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The 32 publications noted in Table 1 ( Falagas and Makris, 2009 ; Manning et al, 2009 ; Kohli, 2013 ; Vandini et al, 2014a , b ; Arvanitakis, 2015 ; La Fauci et al, 2015 ; Caselli et al, 2016 ; Afinogenova et al, 2018 ; Al-Marzooq et al, 2018 , 2019 ; Caselli et al, 2018 ; D'Accolti et al, 2018 , 2019 , 2021 , 2022 , 2023 ; Rodolfi and Caselli, 2018 ; Caselli et al, 2019 ; Dural-Erem et al, 2019 ; Kleintjes et al, 2019 ; Rognoni et al, 2019 ; Caselli and Purificato, 2020 ; Kleintjes et al, 2020 ; Razenberg et al, 2020 ; Stone et al, 2020 ; Tarricone et al, 2020 ; Klassert et al, 2022 ; Soffritti et al, 2022 ; Caselli, 2023 ; Leistner et al, 2023 ; Ramos and Frantz, 2023 ) include an opinion ( Falagas and Makris, 2009 ), two patents ( Manning et al, 2009 ; Rodolfi and Caselli, 2018 ), a commentary ( Caselli and Purificato, 2020 ), a report ( Razenberg et al, 2020 ), two reviews ( D’Accolti et al, 2022 ; Ramos and Frantz, 2023 ), two book chapters ( Kohli, 2013 ; Arvanitakis, 2015 ), three conference abstracts of previously published results ( Al Marzooq et al, 2019 ; Rognoni et al, 2019 ; Caselli, 2023 ), and in vitro assays and hospital-based studies. A total of five publications assessed the efficiency of microbial-based sanitization products using in vitro assays with common healthcare-associated pathogens ( La Fauci et al, 2015 ; D'Accolti et al, 2018 , 2021 ; Dural-Erem et al, 2019 ; Stone et al, 2020 ).…”
Section: Search Strategy and Results Of Literature Overviewmentioning
confidence: 99%
“…The review by Ramos and Fritz conducted in 2023 ( Ramos and Frantz, 2023 ) on the use of microbial-based solutions in hospital-based studies found that the studies demonstrated overwhelmingly positive results, including significant reductions in pathogen burden, antimicrobial-resistant genes, and nosocomial infections, yet the authors stressed that these studies were limited in duration and scope.…”
Section: Main Findings Of Studies Investigating Microbial-based Antim...mentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical disinfectants work well for immediate disinfection, but they can lead to recontamination and favor microorganisms resistant to antibiotics when applied to interior surfaces. A study by Ramoz and Frantz et al [16] found that the use of traditional chemical disinfectants in built environments has significantly increased in reaction to the COVID-19 pandemic. As opposed to the conventional disinfection being used, probiotic-based sanitation (PBS) is predicated on the idea that probiotic bacteria, specifically apathogenic Bacillus spp., can outcompete and drive out infections when mixed with environmentally friendly detergents and sprayed on interior surfaces.…”
mentioning
confidence: 99%